2012
DOI: 10.1590/s1678-77572012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of salivary glycoproteins in aggressive and chronic periodontitis

Abstract: Objectives The aim of this study was to compare the pattern of secretion and the expression of mucin glycoprotein-2 (MG2) and lactoferrin in individuals with or without periodontitis. Material and Methods Five individuals with aggressive periodontitis (APG), 5 with generalized chronic periodontitis (CPG) and 5 without periodontitis (CG) were enrolled after informed consent. Non-stimulated and stimulated submandibular and sublingual saliva was collected and samples analyzed by Western blot probed with specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In the present study, the level of lactoferrin was significantly higher in the high‐responder subgroup at baseline and decreased significantly after treatment (Table ), with a high OR (6.75) and statistical significance ( P = .003) at baseline with respect to the treatment response (Table ). Several studies have shown high levels of lactoferrin in the gingival crevicular fluid of participants with periodontitis, particularly those with aggressive periodontitis, and these levels correlate with a greater PPD . After periodontal treatment, the local PMN activity is down‐regulated, resulting in a significant reduction in the lactoferrin level .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the level of lactoferrin was significantly higher in the high‐responder subgroup at baseline and decreased significantly after treatment (Table ), with a high OR (6.75) and statistical significance ( P = .003) at baseline with respect to the treatment response (Table ). Several studies have shown high levels of lactoferrin in the gingival crevicular fluid of participants with periodontitis, particularly those with aggressive periodontitis, and these levels correlate with a greater PPD . After periodontal treatment, the local PMN activity is down‐regulated, resulting in a significant reduction in the lactoferrin level .…”
Section: Discussionmentioning
confidence: 99%
“…As regards the role of lactoferrin in periodontal disease (Fine, ), higher lactoferrin salivary levels were measured in Australian (Huynh et al., ), Indian (Yadav et al., ), Swedish (Glimvall, Wickstrom, & Jansson, ), Finnish (Suomalainen, Saxen, Vilja, & Tenovuo, ), Taiwanese (Tsai, Kao, & Chen, ; Wei et al., ), American (Fine, Furgang, & Beydouin, ), and British (Adonogianaki, Moughal, & Kinane, ) periodontitis patients with respect to healthy controls, while low lactoferrin level was found among Brazilian (Rocha Dde et al., ) and Chinese (Wu, Shu, Luo, Ge, & Xie, ) periodontitis patients. Finally, among Japanese (Ikuta et al., ), Swedish (Figueredo & Gustafsson, ), and British (Murray, Mooney, & Kinane, ) subjects, no differences between patients with periodontitis and controls were detected.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data, degree of periodontal inflammation correlates with cytokines levels 15 . Furthermore, it has been shown that the degree of the periodontal disease is influenced by secretor status 16,17 .…”
Section: Periodontitismentioning
confidence: 99%